Pengaruh Metode Pendinginan Air, Oli, dan Udara pada Pengelasan SMAW dengan Material Baja ST 37 - Muhammad Yapshi Matondang; Fadly Ahmad Kurniawan Nasution (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Shielded Metal Arc Welding (SMAW) is widely used on low carbon steels such as ST 37, but the quality of the joint is greatly influenced by post-welding treatment, particularly the cooling method. This study aims to analyze the effect of water, oil, and air cooling media on the mechanical properties and hardness of SMAW welds on ST 37 steel. The method used is quantitative experimental research with fixed welding parameters, namely a current of 85 A and an RB E 6013 electrode, while the cooling media are varied. The tests included tensile testing based on ASTM E8, Vickers hardness testing, and microstructure analysis. The results showed that water cooling produced the highest yield strength and hardness (179 HV), but tended to reduce the ability for further plastic deformation. Oil cooling provided more balanced mechanical properties with the highest strain of 17.40% and relatively high tensile strength. Air quenching produced the highest maximum tensile strength of 425.26 N/mm² with good ductility and a lower risk of cracking. The conclusion of this study indicates that air quenching is the most optimal method for SMAW welding of ST 37 steel because it produces stable, ductile, and reliable joints for structural applications.